Analisa Ekonomi Media Radio Gen 103,1 FM - Laras Puspitorini (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
As conventional media, radio must be able to adapt and innovate to continue to attract audiences and maintain its business. One that is considered capable of adapting in the era of digitalization is Gen 103.1 FM, a radio in Surabaya managed by PT. Mahaka Radio Integra Tbk. Based on Nielsen data in January 2023, Gen FM has the largest exclusive listeners compared to other radio stations with the "young" segmentation (aged 20 - 34 years). Apart from that, when compared to other radio stations in Surabaya, Gen 103.1 FM is better able to adapt and take advantage of the digitalization era to improve its business economy. This is not only proven by its large number of followers (13,100), but also by its more varied social media advertising offerings compared to other radio stations. Therefore, it is important to know what Gen 103.1 Fm's business model is so that other radio stations in Indonesia can follow which are now starting to lose listeners. To analyze the Gen 103.1 FM digital radio business model, several literature reviews were used, namely media economics and radio media company business models with qualitative descriptive methods used. Data collection in this research can be collected using in-depth interview techniques with Gen 103.1 FM employees and direct observation of the business model implemented. From the results of this research, it is known that Gen 103.1 FM has a digital economic business model that is strong and different compared to other radio stations.